Workplace Mobbing and Burnout Among a Sample of Nurses - BENABDERRAHMANE, Tahar; KADDOUR, Imed (Journal of Human Sciences, 2025)
The study aimed to identify the correlation between workplace mobbing and burnout from the perspective of a sample of nurses. It also sought to determine the differences in their burnout levels based on variables such as gender, age, and seniority. To achieve the study’s objectives, a descriptive methodology was adopted, and data were collected using the Maslach Burnout Inventory, consisting of 22 items, and a workplace mobbing scale, comprising 46 items. Tools were applied to a non-random purposive sample of 30 nurses at Al-Bir Hospital, Constantine. The study found a positive correlation between workplace mobbing and burnout through dimensions such as: personal reputation defamation, professional reputation defamation, and endangering the victim’s health. No significant differences in the burnout levels among the sample based on age and seniority.